An analysis of the role health personnel, health facilities and family support in increasing pregnant women's interest in antenatal care visits at Kuta Alam health centre - Winda Tri Mutia; Ermi Girsang; Sri Lestari Ramadhani Nasution (SEAN Institute, 2024)
Antenatal Care is one of the pillars supporting safe motherhood in efforts to reduce maternal and fetal morbidity and mortality. WHO estimates that 500,000 pregnant women die from pregnancy-related complications. There are factors that can influence Antenatal Care visits, including the role of health workers and family support. This study aims to analyze the role of health workers and family support in increasing pregnant women's interest in antenatal care visits at the Kuta Alam Community Health Center. This type of research is quantitative analysis using a cross sectional design. The population in this study is mothers who have given birth and had babies during the period September 2020-September 2023, totaling 250 respondents. The results obtained were significant (p=0.002) and there was a relationship between Health Facilities and Antenatal Care visits. The results obtained were significant (p=0.001) and the variables that had an influence in increasing pregnant women's interest in ANC visits at the Kuta Alam Community Health Center were the Health Facilities variable with p value 0.001, OR = 9.333 (95% CI = 3.085) meaning that respondents who stated health facilities had 9.333 times the odds compared to respondents who stated health workers were provided with a B coefficient value of 2.413.